2006
DOI: 10.1007/bf03345538
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of early treatment with insulin glargine in patients with cystic fibrosis and impaired glucose tolerance

Abstract: Diabetes mellitus is an increasing complication of cystic fibrosis (CF), as a result of the improved life expectancy. There is clear association between diabetes and increased morbidity and mortality. Lung function and clinical status deteriorate up to 2-4 yr before the diagnosis of CF-related diabetes (CFRD). The aim of our study was to evaluate the effects, on glucose homeostasis and clinical status, of the early treatment with insulin glargine in CF patients with impaired glucose tolerance (IGT). We selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 9 publications
2
80
1
2
Order By: Relevance
“…However, in the study by Minicucci et al16 there was a 10% decrease in FEV1 in the year prior to the intervention, which may be a bias because even CFRD patients have no such decline in this parameter. Koloušková et al17 and Drummond et al12 , who had a more consistent number of cases, found that FEV1 was lower in the untreated group compared to those treated with insulin, which confirms the results described by Dobson et al6 Bizarri et al20 , and Hameed et al19 …”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…However, in the study by Minicucci et al16 there was a 10% decrease in FEV1 in the year prior to the intervention, which may be a bias because even CFRD patients have no such decline in this parameter. Koloušková et al17 and Drummond et al12 , who had a more consistent number of cases, found that FEV1 was lower in the untreated group compared to those treated with insulin, which confirms the results described by Dobson et al6 Bizarri et al20 , and Hameed et al19 …”
Section: Discussionsupporting
confidence: 55%
“…The authors assumed that participation in the study made patients more aware of their change in glucose metabolism, leading to better nutritional behavior. Most other studies6 , 17 - 20 showed positive results, but the insulin doses used were higher.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Moreover, there is now persuasive evidence that the decline in nutritional and pulmonary status occurs 2-6 years before the diagnosis of CFRD, when postprandial hyperglycaemia is less marked [5,6]. This suggests that even 'early' carbohydrate intolerance, with relatively modest postprandial glycaemic excursions, is metabolically detrimental to pulmonary function.…”
Section: Cfrd Prevalence and Significancementioning
confidence: 99%